Step * 1 1 1 1 of Lemma iterate-rotate-rotate-by

.....subterm..... T:t
2:n
1. : ℕ
2. : ℤ
3. ¬i < 1
4. 0 < i
5. rot(n)^i rotate-by(n;i 1) ∈ (ℕn ⟶ ℕn)
6. : ℕn
7. ((x (i 1) rem n) (1 rem n) rem n) ((x (i 1)) rem n) ∈ ℤ
⊢ if (x (i 1) rem =z 1) then else (x (i 1) rem n) fi  ((x (i 1) rem n) (1 rem n) rem n) ∈ ℤ
BY
(MoveToConcl (-1) THEN CaseNat `n') }

1
1. : ℕ
2. : ℤ
3. ¬i < 1
4. 0 < i
5. rot(n)^i rotate-by(n;i 1) ∈ (ℕn ⟶ ℕn)
6. : ℕn
7. 1 ∈ ℤ
⊢ (((x (i 1) rem 1) (1 rem 1) rem 1) ((x (i 1)) rem 1) ∈ ℤ)
 (if (x (i 1) rem =z 1) then else (x (i 1) rem 1) fi 
   ((x (i 1) rem 1) (1 rem 1) rem 1)
   ∈ ℤ)

2
1. : ℕ
2. : ℤ
3. ¬i < 1
4. 0 < i
5. rot(n)^i rotate-by(n;i 1) ∈ (ℕn ⟶ ℕn)
6. : ℕn
7. ¬(n 1 ∈ ℤ)
⊢ (((x (i 1) rem n) (1 rem n) rem n) ((x (i 1)) rem n) ∈ ℤ)
 (if (x (i 1) rem =z 1) then else (x (i 1) rem n) fi 
   ((x (i 1) rem n) (1 rem n) rem n)
   ∈ ℤ)


Latex:


Latex:
.....subterm.....  T:t
2:n
1.  n  :  \mBbbN{}
2.  i  :  \mBbbZ{}
3.  \mneg{}i  <  1
4.  0  <  i
5.  rot(n)\^{}i  -  1  =  rotate-by(n;i  -  1)
6.  x  :  \mBbbN{}n
7.  ((x  +  (i  -  1)  rem  n)  +  (1  rem  n)  rem  n)  =  ((x  +  (i  -  1))  +  1  rem  n)
\mvdash{}  if  (x  +  (i  -  1)  rem  n  =\msubz{}  n  -  1)  then  0  else  (x  +  (i  -  1)  rem  n)  +  1  fi 
=  ((x  +  (i  -  1)  rem  n)  +  (1  rem  n)  rem  n)


By


Latex:
(MoveToConcl  (-1)  THEN  CaseNat  1  `n')




Home Index